2022
DOI: 10.3389/fgwh.2022.644591
|View full text |Cite
|
Sign up to set email alerts
|

Are UK Policies and Practices for Regulated Donor Insemination Forcing Women to Find Unregulated Sperm Donors Online? A Perspective on the Available Evidence

Abstract: In recent years, there has been an increase in women obtaining donor sperm via unregulated websites and social media. In this article, we bring together the disparate evidence in this emerging field to consider whether restrictive UK policies and practices for regulated clinical donor insemination (DI) are a potential explanation for the growing use of the currently unregulated, online route to donor insemination. To this end, we examine the nature of the National Institute for Health and Care Excellence (NICE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Moreover, there is strong evidence of indirect discrimination of some groups through funding rules even when they are given legal access (Taylor et al, 2022).…”
Section: Strengthsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, there is strong evidence of indirect discrimination of some groups through funding rules even when they are given legal access (Taylor et al, 2022).…”
Section: Strengthsmentioning
confidence: 99%
“…Recipients indicated that the high cost of donor sperm in clinics and sperm banks is a prime motive for looking elsewhere (Jadva et al, 2018). When no reimbursement is offered, the costs of donor insemination may be very high, especially since the success rate per insemination is below 15 percent (Kupka et al, 2016;Taylor et al, 2022). As a consequence of the shortage of sperm donors in most countries (apart from Denmark), there are fewer donors to choose from (if recipients are allowed to do so) or to match.…”
Section: Strengthsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, many couples have turned to inexpensive and less constrained alternatives such as seeking care abroad via “reproductive tourism” [ 5 ]. In the setting of donor insemination, women may turn to unscreened and unregulated sperm donors for financial reasons [ 6 ]. In addition to the cost, the global Coronavirus pandemic, restrictions, and invasive nature of ART, with frequent transvaginal ultrasounds and on-demand sperm production, have driven many couples seeking reproductive care to in-home alternatives that utilize health technology or “telehealth” [ 7 ].…”
mentioning
confidence: 99%